Safe sex negotiation and HIV risk reduction among women: A cross-sectional analysis of Burkina Faso 2021 Demographic and Health Survey. - Sulemana Ansumah Saaka; Cornelius K A Pienaah; Zakara Stampp; Roger Antabe (Public Library of Science (PLoS), 2024)
Women are biologically more susceptible to the Human Immunodeficiency Virus (HIV) and other sexually transmitted Infections (STIs) because receptive sex is riskier than insertive. Despite condom use being the staple preventive method for HIV infection (over 80% efficacy), in Sub-Saharan African countries like Burkina Faso, a high burden of HIV and the unmet need for condom use coexist. Moreover, even though women in SSA are disproportionately HIV positive, they are reportedly less capable of negotiating condom use for HIV risk reduction. Thus, using the Health Believe Model (HBM), this study explored the factors that influence condom use among women within the context of HIV prevention, with a key interest in condom use negotiation. Using the women's dataset of the 2021 Burkina Faso Demographic and Health Survey and applying logistic regression models, this study examined the factors associated with condom use for HIV risk reduction. Women who had confidence to negotiate condom use with their partners (OR = 1.57, P<0.001, 95%CI: 1.29, 1.91), those with secondary education (OR = 1.38, P<0.05, 95%CI: 1.07 1.77), from richest households (OR = 1.64, P<0.05, 95%CI: 1.08, 2.47), the employed (OR = 1.23, P<0.05, 95%CI: 1.02, 1.49), women with knowledge of sexually transmitted infections (OR = 1.58, P<0.001, 95%CI: 1.26, 1.97), those who have ever been tested for HIV (OR = 1.85, P<0.001, 95%CI: 1.52 2.24), as well as those who knew that a healthy-looking person can have HIV (OR = 2.64, P<0.001, 95%CI: 2.15, 3.24) were all significantly more likely to practice condom use for HIV risk reduction. Also, religion and geographical location of participants significantly predicted condom use for HIV risk reduction in the study context. The ability to negotiate condom use, knowledge of HIV and STIs, the socioeconomic status of women, as well as their geographical location, influence their practice of safer sex for HIV risk reduction in Burkina Faso.